PENDIDIKAN KARAKTER DALAM PERSPEKTIF AL-QUR'AN DAN SUNNAH GUNA MENINGKATKAN MUTU BINA PRIBADI PADA PESERTA DIDIK DI MADRASAH IBTIDAIYAH(MI) YPI BATUMARTA - Faruq Amin; Supatmi; Muhammad Yasin (UNISAN JURNAL, 2023)
This study aims to evaluate the implementation of character education at MI YPI Batumarta, as well as the factors that influence the effectiveness of character education implementation and the efforts that can be made by teachers and the school to improve the quality of character building for students. The method used is a case study with data collection techniques through observation, interviews, and documentation. The results show that the implementation of character education at MI YPI Batumarta has produced positive results in shaping students' noble and ethical characters. However, there are several obstacles faced, such as a lack of support from parents and inadequate supporting resources. To overcome these obstacles, efforts can be made by teachers and the school, such as developing an integrated character education program, involving parents in the program, providing adequate supporting resources, developing character assessments, and organizing extracurricular activities that support character education. With these efforts, it is hoped that the quality of character building for students through character education at MI YPI Batumarta in the academic year 2022/2023 can be improved and students can become noble and ethical individuals who can contribute positively to society.